2004
DOI: 10.1093/occmed/kqh003
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and coping strategies as risk factors for the development of non-specific work-related upper limb disorders (WRULD)

Abstract: Alongside physical and psychosocial work-related factors, psychoneuroticism and neurotic perfectionism appear to be important risk factors for developing non-specific WRULD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 14 publications
2
26
0
2
Order By: Relevance
“…Possibly this is the stimulus as to why computer workers with non-specific upper limb disorders and showing pain catastrophizing behavior, not only develop, but are "painfully" aware of their upper limb disorders. In our study the role of pain catastrophizing overruled the impact of neurotic perfectionism and anxiety, found in earlier studies as risk factors 9,10) . Contrary to the study of Hamberg-van Reenen et al 5) which showed inconclusive evidence for the relationship between low physical capacity and future musculoskeletal pain in a large prospective cohort study, we found an association between lower physical fitness and early non-specific WRULD.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Possibly this is the stimulus as to why computer workers with non-specific upper limb disorders and showing pain catastrophizing behavior, not only develop, but are "painfully" aware of their upper limb disorders. In our study the role of pain catastrophizing overruled the impact of neurotic perfectionism and anxiety, found in earlier studies as risk factors 9,10) . Contrary to the study of Hamberg-van Reenen et al 5) which showed inconclusive evidence for the relationship between low physical capacity and future musculoskeletal pain in a large prospective cohort study, we found an association between lower physical fitness and early non-specific WRULD.…”
Section: Discussionsupporting
confidence: 72%
“…A large cross-sectional study among bank employees showed that job stress was strongly associated with the development of upper limb disorders 8) . With respect to psychological risk factors, especially overcommitment 4,7) , psycho neuroticism and neurotic perfectionism 9) showed a relationship with the onset of upper limb disorders. In a study among PhD students with upper limb disorders it had been shown that a high score on the Trait Anxiety Inventory (STAI 2) was associated with sooner absenteeism from work and self-perceived disability 10) .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The muscle blood flow was then measured by analyzing the slope of the total hemoglobin signal, being the sum of the oxyhemoglobin and deoxyhemoglobin (in mL/min/100 mL). 30,31 Local muscle oxygen consumption was determined at baseline and at 10%, 20%, and 40% of MVC. The oxygen consumption was measured by inflating the blood pressure cuff to 250 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is described in detail elsewhere. [29][30][31] Briefly, this technique is based on the relative transparency of tissue for light in the near-infrared region and on the oxygen-dependent absorption changes of hemoglobin and myoglobin. As one cannot distinguish between myoglobin and hemoglobin, the combined effect of these 2 substances is studied.…”
Section: Measuring Hemoglobin Oxygenationmentioning
confidence: 99%